2017
DOI: 10.1088/2043-6254/aa92b1
|View full text |Cite
|
Sign up to set email alerts
|

Red tea leaves infusion as a reducing and stabilizing agent in silver nanoparticles synthesis

Abstract: Due to the unique properties of silver nanoparticles there is growing interest in their applications. Current trends in nanotechnology are focused on developing a new technique to synthesize nanoparticles using biological methods associated with the use of plant extracts, fungi, bacteria or essential oils. These methods are a promising alternative to conventional approaches which can minimize the use of hazardous substances. The silver nanoparticles synthesis using red tea infusion as a reducing and stabilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Many of these methods involve the use of harmful, costly and toxic substances and are eco-unfriendly [18]. Now a days emphasis has been given on the biosynthesis of the AgNPs which includes bacteria, fungi, essential oils [19], nucleic acid [20] yeast, algae and plant extract [21]. The latter has been given utmost importance for easily available, low maintenance [22], cost effective, less toxic and environmentally friendly properties [23].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these methods involve the use of harmful, costly and toxic substances and are eco-unfriendly [18]. Now a days emphasis has been given on the biosynthesis of the AgNPs which includes bacteria, fungi, essential oils [19], nucleic acid [20] yeast, algae and plant extract [21]. The latter has been given utmost importance for easily available, low maintenance [22], cost effective, less toxic and environmentally friendly properties [23].…”
Section: Introductionmentioning
confidence: 99%
“…Plant extracts are reported to be stabilizers and reducers in synthesizing nanoparticles, resulting in uniformly sized nanoparticles without forming aggregates [9]. Generally, plant extracts that contain polyphenols are suitable for use as conjugated ligands to stabilize the surface energy of nanoparticles [12]. Black tea contains polyphenol compounds theaflavin and thearubigins that are worthy of being proposed as conjugating agents in this study [13].…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 86%
“…The SEM studies revealed that the synthesized Ag‐NPs were spherical, and size nanoparticles were 27.3 nm. [ 61 ] The metal nanoparticle solutions were obtained by reacting AgNO3 aqueous solution with aqueous NaHCO 3 and tea leaf extracts silver nanoparticles prepared from the green tea were characterized using SEM and TEM, The synthesized nano crystallites of Ag were in the ≈30 nm. Then, cotton fabrics fixed with nanoparticles were prepared, which showed high antibacterial activity and distinctive color, showing potential for application as anti‐microbial dyes.…”
Section: Factors Responsible For the Evolution Of Nanoparticles With Teamentioning
confidence: 99%